1971
DOI: 10.2466/pms.1971.33.3.887
|View full text |Cite
|
Sign up to set email alerts
|

Noise-Induced Arousal and Breadth of Attention

Abstract: The effect of intermittent noise upon attention span was investigated in two experiments. In Exp. 1, 4 levels of noise intensity were used (no noise, 75 db, 85 db, and 100 db). The task was a serial anticipation task in which the relevant stimuli were 4-letter words located in the center of a projected slide. 3-letter words were peripherally located; the peripheral words were not mentioned to Ss. Ss in the 85-db and the 100-db conditions learned fewer of the peripheral words as indicated by a free-recall test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 11 publications
3
35
1
Order By: Relevance
“…Furthermore, conflicting results are obtained on the Stroop test when arousal is manipulated by the use of noise (Broadbent, in press) or drugs. O'Malley and Poplawsky (1971) reported an improvement in performance for incongruent stimuli in 85-dB noise, but there was a similar improvement in color naming. Hartley and Adams (1974) found increased interference in lOO-dB noise in their first experiment, but in a second experiment, where exposure duration and practice were assessed independently, the brief exposure to 95-dB noise was beneficial and decreased interference, and the long exposure increased interference, suggesting a cumulative adverse effect of noise.…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, conflicting results are obtained on the Stroop test when arousal is manipulated by the use of noise (Broadbent, in press) or drugs. O'Malley and Poplawsky (1971) reported an improvement in performance for incongruent stimuli in 85-dB noise, but there was a similar improvement in color naming. Hartley and Adams (1974) found increased interference in lOO-dB noise in their first experiment, but in a second experiment, where exposure duration and practice were assessed independently, the brief exposure to 95-dB noise was beneficial and decreased interference, and the long exposure increased interference, suggesting a cumulative adverse effect of noise.…”
Section: Discussionmentioning
confidence: 93%
“…[54] The Stroop task is a much more complex task that measures inhibition of pre-potent response along with selective attention and processing speed and is seen as a "general indicator of cognitive fl exibility and control" [p. 231, 50]. Some studies report less interference (reduced cognitive inhibition) as a result of noise, [3,61] while others fi nd no effect. [56] This inconsistency may be partly due to the varied duration and characteristics of the noise used.…”
Section: Noise Stress and Mental Fl Exibility And Inhibition Of Pre-pmentioning
confidence: 98%
“…Several studies have suggested that the noise disruption effects on task performance may depend on the level of arousal induced by noises [17][18]. For example, compared to silent environment, participants performed better in the Rod-and-Frame test and in the Stroop test when listening to low arousal noises [19][20]. A popular theory explaining the noise effects on arousal is the attentional narrowing mechanism [21].…”
Section: Introductionmentioning
confidence: 99%
“…A popular theory explaining the noise effects on arousal is the attentional narrowing mechanism [21]. It suggests that noises increase arousal and the increased arousal, in turn, decreases the breadth of attention [19], [22]. More specifically, when at a relatively low arousal level, proper attentional narrowing helps to exclude irrelevant cues and thus would facilitate performances.…”
Section: Introductionmentioning
confidence: 99%